Differential microRNA profiling of the Marshallese population in Arkansas reveals a higher association with chronic diseases - Gohar Azhar; Ambika Verma; Pankaj Patyal; Wei Zhang; Shakshi Sharma; Patricia E. Savary; Sheldon Riklon; Philmar Mendoza Kabua; Pearl A. McElfish; Jeanne Y. Wei (PLoS ONE, 2025)
The Marshallese communities face disproportionately high prevalence of chronic diseases, including diabetes, obesity, cardiovascular disease, and inflammatory conditions. Differences in miRNA expression may contribute to investigate the potential risk of chronic diseases in Marshallese people. In this study, we used RNA isolated from blood samples of Marshallese participants that resides in Arkansas to perform miRNA expression profiling and differential expression analysis. Specifically, blood samples were collected from 47 Marshallese participants after obtaining written informed consent and were subjected to Illumina-based next-generation RNA sequencing. Using the miRBase database, we identified the miRNAs that were most significantly expressed based on log2 fold change values, applying a Bonferroni-corrected P-value threshold of < 0.01. We found that a total of 63 human miRNAs were differentially expressed in the Marshallese subjects, with 52 miRNAs significantly upregulated and 11 miRNAs downregulated in males compared with females. Notably, 2 miRNA families, hsa-miR-548 and hsa-let-7, were significantly upregulated in the Marshallese population and are known to play important roles in regulating inflammatory responses. Further analysis revealed the 25 miRNAs that had the largest significant difference in expression with a cutoff of 1.5 when comparing males with females. Among these, we observed that 7 miRNAs were upregulated, and 18 miRNAs were downregulated by greater than 1.5 log2 fold change in males versus females. Interestingly, upregulated expression of hsa-miR-548k in males and hsa-miR-496 in females were both associated with diabetes mellitus. Diabetes remains a major health concern in the Marshallese community and may accelerate comorbidities related to cardiovascular conditions and cognitive decline. Therefore, the specific roles of these miRNAs in relation to these health issues warrant further investigation.